2021
DOI: 10.1177/1052684621990618
|View full text |Cite
|
Sign up to set email alerts
|

School Administrators and Physical Educators: A Scoping Review of Perceptions and Partnerships From 2000 to 2020

Abstract: Physical education (PE) is an academic subject that delivers students a standards-based program designed to foster the knowledge and skills needed to be physically active for a lifetime. Although there is a dearth of research that has examined school administrators’ perceptions and interactions with PE, it has been reported that school administrators often are a barrier that disrupts effective PE programming. This study aimed to conduct a scoping review of the literature to capture a comprehensive view of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This is especially important given that many adapted physical educators have expressed that there is a lack of collaboration between other school personnel and themselves. For instance, it has been reported that PE is seldom addressed adequately throughout the IEP process (Chaapel et al, 2013;Columna et al, 2014;McNamara et al, 2021aMcNamara et al, , 2021b. In addition, some physical educators may only be allowed to view a student's IEP and provide feedback, rather than attend the IEP meeting (Columna et al, 2014).…”
Section: Adapted Physical Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially important given that many adapted physical educators have expressed that there is a lack of collaboration between other school personnel and themselves. For instance, it has been reported that PE is seldom addressed adequately throughout the IEP process (Chaapel et al, 2013;Columna et al, 2014;McNamara et al, 2021aMcNamara et al, , 2021b. In addition, some physical educators may only be allowed to view a student's IEP and provide feedback, rather than attend the IEP meeting (Columna et al, 2014).…”
Section: Adapted Physical Educationmentioning
confidence: 99%
“…School administrators have a critical responsibility to ensure students with disabilities receive educational services to meet their educational needs, including students who are entitled to and qualify for APE. While recent surveys assessed school administrators' opinions toward APE, researchers acknowledged this line of research has been neglected (Bittner et al, 2020;McNamara et al, 2020;McNamara et al, 2021aMcNamara et al, , 2021b. In addition, the few available studies did not use a theoretical model to develop their surveys.…”
Section: Purposementioning
confidence: 99%
“…This apparent lack the knowledge of APE aligns with previous research that has continually demonstrated this group, and school administrators in general, have a poor conceptualization of these services, how APE and PE fit within the special education process, and PE as a curriculum (e.g. McNamara et al, 2021bMcNamara et al, , 2022. To effectively supervise and provide leadership, school administrators need a strong grasp of the variety of subjects taught within their schools (Lochmiller and Acker-Hocevar, 2016).…”
Section: Discussionmentioning
confidence: 70%
“…Maher, 2017Maher, , 2018. Further, it has primarily centered on delivering inclusive PE experiences, rather than on APE services and teachers defined and mandated through US special education legislation (McNamara et al, 2021b). The research in the US has either focused exclusively on the perspectives of APE teachers (McNamara et al, in press) or has been simple descriptive survey research that, unlike qualitative research, is unable to provide participants' perspectives depicting a more holistic view of their attitudes and rationale for their values toward APE services and teachers (Bittner et al, 2020;McNamara et al, 2021a;Nassaji, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation